A Mass Transfer-Based Method for Controlled Electrosynthesis and Organization of Tetrathiafulvalene Bromide Micro/Nanowires. Issue 2 (1st January 2019) - Gunasekera, Disni; Kilani, Mohamed; Yu, Xuecheng; Chen, Qianjin; Mao, Guangzhao; Luo, Long
Abstract : Nanowire sensors are promising to deliver greater performance than conventional sensors due to their size confinement as well as low cost and power consumption. However, scalable assembly of nanowire sensors remains a big challenge, which requires the synthesis of uniform nanowires and organization of them. Here, we report a simple method to control the growth and organization of a promising nanowire material for gas sensing, tetrathiafulvalene bromide ((TTF)Br), by mass transfer in electrodeposition. We found that the use of Pt microdisk electrodes for electrodeposition of (TTF)Br wires resulted in wires with higher uniformity and larger aspect ratio (length to width) than their counterparts deposited on Pt films under the same deposition conditions. More interestingly, we found that the number of wires grown from a Pt microdisk electrode exhibited a limiting number of 3 or 4 per electrode when the electrode diameters are smaller than ∼1.4 μm. Both experimental and simulation results suggest that the morphological differences and the constant minimum wire density are caused by the different TTF flux distributions at a microdisk versus a film electrode. The results have significant implications for scalable manufacturing of nanowire-based sensing devices.